Synthesis and Applications of Compartmentalised Molecular Polymer Brushes. Issue 24 (14th May 2018) - Pelras, Théophile; Mahon, Clare S.; Müllner, Markus
Abstract: Polymer science is rapidly advancing towards the precise construction of synthetic macromolecules of formidable complexity. Beyond the impressive advances in control over polymer composition and uniformity enabled by the living polymerisation revolution, the introduction of compartmentalisation within polymer architectures can elevate their functionality beyond that of their constituent parts, thus offering immense potential for the production of tailor‐made nanomaterials. In this Minireview, we discuss synthetic routes to complex molecular brushes with discrete chemical compartments and highlight their potential in the development of advanced materials with applications in nanofabrication, optics and functional materials. Abstract : Hairy compartments : The methodical compartmentalisation of molecular polymer brushes offers immense opportunity to develop tailor‐made advanced nanomaterials with applications in nanofabrication, optics and functional materials.